2015
DOI: 10.1016/j.yrtph.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk characterization of petroleum coke calcining facility emissions

Abstract: Calcining processes including handling and storage of raw petroleum coke may result in Particulate Matter (PM) and gaseous emissions. Concerns have been raised over the potential association between particulate and aerosol pollution and adverse respiratory health effects including decrements in lung function. This risk characterization evaluated the exposure concentrations of ambient air pollutants including PM10 and gaseous pollutants from a petroleum coke calciner facility. The ambient air pollutant levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Similar to the results of the fence line monitoring and air dispersion modeling, our assessment of off-site environmental media indicates that potential community exposures to petcoke are minimal. A recent risk characterization of a petcoke handling and calcining facility has reached similar conclusions to those presented in this study (Singh et al, 2015). We found that deposition and accumulation of petcoke in off-site locations in neighborhoods abutting the facility, if any, is insufficient to alter concentrations of trace elements and PAHs in the soil and on surfaces examined.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the results of the fence line monitoring and air dispersion modeling, our assessment of off-site environmental media indicates that potential community exposures to petcoke are minimal. A recent risk characterization of a petcoke handling and calcining facility has reached similar conclusions to those presented in this study (Singh et al, 2015). We found that deposition and accumulation of petcoke in off-site locations in neighborhoods abutting the facility, if any, is insufficient to alter concentrations of trace elements and PAHs in the soil and on surfaces examined.…”
Section: Discussionsupporting
confidence: 88%
“…The AMS/EPA regulatory model (AERMOD) was widely used by researchers in many studies, including dispersion modeling for various pollutants such as SO 2 , NOx, PM 2.5 , PM 10 , mercury, etc. [19][20][21][22][23][24][25][26]. AERMOD has also been compared to other dispersion models, including CALPUFF and ADMS [27][28][29][30][31], and coupled with the WRF model to analyse sensitivity to metrological conditions associated with PM dispersion calculations [32][33].…”
mentioning
confidence: 99%